Peran Orangtua Asuh Dalam Pembentukan Akhlak Anak - Hazriyanti, Irma; Nurjanah, Nurjanah; Murniyetti, Murniyetti (An-Nuha, 2024)
Parents are the first educators and mentors for children and have a big influence on their development. This affects the child's future, if the child is educated well then the results will be good too, and vice versa. Morals are the main foundation in forming a child's personality. Continuous coaching is needed to create good morals in children. Likewise, the role of foster parents is essentials in shaping the morals of children in orphanages. This research aims to discover the role of foster parents in forming morals and the supporting and inhibiting factors for foster parents in forming the morals of children in orphanages. This research uses a qualitative method with a case study approach. The results of the research show that 1) In the formation of children's morals at the Jasmine Nabila Inayah Ulak Karang Orphanage, there are four roles of foster parents, namely a. Foster Parents as Caregivers, b. Foster Parents as Educators, c. Foster Parents as Role Models, d. Foster Parents as Foster Parents. 2) Supporting and inhibiting factors for foster parents in forming children's morals at the Jasmine Nabila Inayah Ulak Karang Orphanage. The supporting factors are internal factors (Caregiver Experience, Caregiver Communication Skills, Caregiver Patience and Love, Creativity in Caregiving, and Personal Example) as well as external factors (Social Service Support, Donor Support, Volunteer Involvement, No exposure to gadgets). The inhibiting factors are internal factors (limited time and attention of caregivers, poor background of the child, unstable emotional and psychological condition of the child, bad character of the child) and external factors (negative influence from the environment outside the institution, financial condition of the institution unstable, inadequate facilities and infrastructure, no special recruitment for caregivers).